Polyploidization and Cancer - Poon, Randy Y.C (Advances in Experimental Medicine and Biology, 2010)
Limiting genome replication to once per cell cycle is vital for maintaining genome stability. Although polyploidization is of physiologically importance for several specialized cell types, inappropriate polyploidization is believed to promote aneuploidy and transformation. A growing body of evidence indicates that the surveillance mechanisms that prevent polyploidization are frequently perturbed in cancers. Progress in the past several years has unraveled some of the underlying principles that maintain genome stability. This book brings together leaders of the field to overview subjects relating to polyploidization and cancer.